Integrated method for global land cover products' validation on the example of Bulgaria - Stamenova, Vanya; Stamenov, Stefan (Acta geographica Slovenica, 2022)
The article presents the validation of four global land cover datasets for 2009–2010 (GlobeLand30, GlobCover, Forest/Non-forest map, Tree canopy cover) for the territory of Bulgaria as a part of a task led by the Group on Earth Observation (GEO). An integrated method for validation, combining the GIS processing capabilities, various data and the expert knowledge-based method of visual interpretation was developed. It aims to be an effective, time-saving approach, allowing validation of several datasets in one environment. The results are presented in vector format with structured attribute data for all validated datasets. The analysis reveals that the highest accuracy is observed for Tree canopy cover (96.1%), the lowest for GlobCover 2009 (51.0%), and the other products’ accuracy is considerably high, about 80.0%.